Atypical Expression and Activation of GluN2A- and GluN2B-Containing NMDA Receptors at Ganglion Cells during Retinal Degeneration. (21st November 2018) - Yee, Christopher W.; Ivanova, Elena; Toychiev, Abduqodir H.; Willis, Dianna E.; Sagdullaev, Botir T.
Highlights: Phasic recruitment of distinct glutamate receptors is essential for visual discrimination. The fidelity of this fundamental mechanism under aberrant activity, a common pathophysiology, is not known. Aberrant activity leads to pathway-specific alterations in NMDA receptor subunit composition and function. Abstract: Cellular communication through chemical synapses is determined by the nature of the neurotransmitter and the composition of postsynaptic receptors. In the excitatory synapse between bipolar and ganglion cells of the retina, postsynaptic AMPA receptors mediate resting activity. During evoked response, however, more abundant and sustained levels of glutamate also activate GluN2B-containing NMDA receptors (NMDARs). This phasic recruitment of distinct glutamate receptors is essential for visual discrimination; however, the fidelity of this basic mechanism under elevated glutamate levels due to aberrant activity, a common pathophysiology, is not known. Here, in both male and female mice with retinal degeneration ( rd10 ), a condition associated with elevated synaptic activity, we reveal that changes in synaptic input to ganglion cells altered both composition and activation of NMDARs. We found that, in contrast to wild type, the spontaneous activity of rd10 cells was largely NMDAR-dependent. Surprisingly, this activity was driven primarily by atypical activation of GluN2A -containing NMDARs, not GluN2B-NMDARs. Indeed, immunohistochemical analyses and Western blot showed greater levels of the GluN2A-NMDAR subunit expression in rd10 retina compared to wild type. Overall, these results demonstrate how aberrant signaling leads to pathway-specific alterations in NMDAR expression and function.